PENINGKATAN KINERJA GURU DALAM MENGADAKAN VARIASI GAYA MENGAJAR MELALUI IMPLEMENTASI SUPERVISI KLINIS KEPALA SEKOLAH DI SMA NEGERI 1 BENGKULU SELATAN - Agustinus Suharto (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2015)
This study is an action research school in which researchers directly involved in the study to provide guidance and coaching as well as observing teachers in the holding variety of teaching styles that are implemented through clinical supervision activities at school. The main purpose of this school action research was to determine the clinical supervision of the implementation of the Principal in improving teacher performance in a variety of teaching styles held appropriately and effectively in SMAN 1 South Bengkulu in the academic year 2014/2015. Based on the results of mentoring and coaching principals and discussion on the implementation of clinical supervision can be concluded that: (1) Performance of teachers in conducting teaching style variation through the implementation of clinical supervision activities showed an increase in each cycle. The value of teachers' performance through the implementation of clinical supervision principals at each cycle showed an increase in yield. The achievement of performance indicators ≥85% of teachers in conducting teaching style variation of 58.33% with an average of 58.33 in the first cycle increased to 75% with an average of 79.67 in the second cycle and 91.67% with a mean 87.33 average in III. Thus fostering the implementation of clinical supervision on the performance of teachers in conducting teaching style variation in SMAN 1 South Bengkulu in general can be said to be effective because it can improve the performance of teachers and quality of teaching in schools.